Protection Of Women's And Children's Rights In Unregistered Marriage (Nikah Sirri): Reconstructing Maqāṣid Al-Sharī‘ah In The Harmonization Of Islamic Law And Indonesian National Law - Aprinelita Aprinelita; Jumni Nelli (Balai Diklat Keagamaan Bandung, 2026)
Marriage is a sacred institution involving two individuals who commit to living together and building a family. Accordingly, marriages should be officially registered and documented within the state’s legal system. However, there has been a growing prevalence of unregistered marriages (nikah sirri), which fulfill the requirements of validity under religious law but are not recorded by the state’s legal administration. Such marriages pose significant legal and social risks, particularly for women and children. This study aims to examine the extent of legal protection afforded to women and children born from unregistered marriages. It employs a qualitative method using a Maqāṣid al-Sharī‘ah analytical framework to explore the issue. The findings indicate that unregistered marriages, which lack state recognition, often lead to various legal vulnerabilities. These risks may be mitigated through increased awareness and understanding among couples engaging in such marriages. Furthermore, Law Number 1 of 1974 concerning Marriage, as the primary legal framework governing marriage in Indonesia, has not yet fully accommodated adequate protection for wives and children born from unregistered marriages.